Controle de cascudinho Alphitobius diaperinus (Panzer) em cama de aviário perante exposição a micro-ondas eletromagnéticas - Costa, Taynara Stopassoli da (2018)
The Brazilian production of chicken meat has gradually increased in recent years, so the improvement of the production system is of paramount importance to give quality to the final product and agility in its processing. However, one of the problems frequently found in aviaries is the high incidence of Alphitobius diaperinus (Panzer), known as birdwatcher, being one of the main vectors of disease-causing pathogens. Therefore, it is extremely important to control this insect in the production environment, which currently has chemical, physical and biological methods to perform environmental decontamination. In the present work, the action of the electromagnetic microwaves was evaluated by means of three treatments considering time of exposition starting with 5 seconds and gradual increase, using 100%, 80% and 50% of the total power of the furnace, dividing the treatments in three distinct proportions being: thin, intermediate and deep thickness of the aviary bed, with respective values of 10, 15 and 20 cm. Mortality results of larval and adult individuals were obtained only when they were exposed to irradiation with a duration of 15 seconds referring to bed thicknesses, considering 100% of irradiation potential. To complement the study, tests were performed to reach 100% of the mortality rate of the individuals in the two phases of the life cycle evaluated. 100% of the irradiation potential was used to obtain the minimum exposure time: 30 seconds for thickness of 10 cm, 45 seconds for 15 cm and 65 seconds for 20 cm.